Prevalence and assessment of traumatic brain injury in prison inmates: A systematic PRISMA review. (23rd August 2016) - Allely, C. S.
Abstract: Objectives : The primary objectives of the present systematic PRISMA review were: (1) to explore the range of prevalence of TBI in offenders and whether this is higher than in a control sample; (2) to determine which screening measures are available and evaluate the evidence on these; and, lastly, (3) to evaluate whether prevalence of TBI is associated with increased prevalence of other health conditions and/or offending behaviour. Methods : The present systematic PRISMA review explores the peer-reviewed literature published since 2005 which has investigated TBI in incarcerated populations using five databases (CINAHL, MEDLINE, PsycARTICLES, Psychology and Behavioral Sciences Collection, PsycINFO) in addition to separate searches conducted on 'Google Scholar' using specific search criteria. Results : Seventeen studies were identified which explored the prevalence of TBI in inmates. Only five of the seventeen studies which investigated prevalence of TBI in offender populations looked at juvenile offending. Interestingly, only seven of the 17 studies included both male and female samples (two of which did not report findings separately for males and females). In terms of the assessments used to investigate prevalence, three studies investigated the prevalence of TBI using The Ohio State University (OSU) TBI Identification method (OSU-TBI-ID). Nine studies used one or two questions in order to elicit information on whether the offender had previously experienced a TBI. Only two studies used the Traumatic Brain Injury Questionnaire (TBIQ). One study used the Brain Injury Screening Index (BISI). One study investigated patients discharged from non-federal South Carolina Emergency Departments or hospitals with a TBI-related ICD-9-CM code. Lastly evidence of TBI checklist from medical record (14 items) was used in one study. Conclusions : In terms of the implication for further research and practice, the studies identified in this review clearly emphasize the need to account for TBI in managing care in offender populations, which may contribute to reduction in offending behaviours. Additionally, there is a need for further research investigating the clinical utility of screening tools for detecting TBI in offender populations such as The Traumatic Brain Injury Questionnaire (TBIQ), The Brain Injury Screening Index (BISI) and The Ohio State University (OSU-TBI-ID) TBI Identification method.